‘Is there Anything Else You’d Like to Say About Community Relations?’ Thematic Time Series Analysis of Open-ended Questions From an Annual Survey of 16- Year Olds - Kelly, Grace; McKnight, Martina; Schubotz, Dirk (methods, data, analyses, 2021)
Since 2003, respondents to the annual Young Life and Times (YLT) survey have been offered an opportunity to give their thoughts on community relations in Northern Ireland. To date, approximately 4,000 comments have been received. This paper reports on a systematic approach to a content analysis of this question. Our methodological aim is to demonstrate the analytic processes involved in creating a coding scheme and to show how a structured content analysis of these responses can complement the published quantitative survey findings, and, in turn, provide a more nuanced understanding of young people’s views on community relations in Northern Ireland over time. By doing so, we feel we also afford a sense of agency to respondents by integrating their opinions and emotions, which ranged from hope to despair, expressed outside the pre-determined survey content, as important data. Our approach shows that a meaningful combination of interpretive and deductive methods can demonstrate the added value that open-ended questions can have for a standardised survey instrument.